Seguimiento de la regeneración natural de alcornoque bajo condiciones microecológicas diferentes. (II Congreso Forestal Español, 1997)
This paper studies the natural regeneration of cork-oak in the forests of Aljibe mountains (Málaga, Spain). A plot for monitoring the development of cork-oak seedlings was installed at Cortes de la Frontera cork-oak forests, under different microecological conditions. To get a plentiful and healthy stock of seedlings is necessary enclose the area and to have a light crown cover, is the main conclusion.